A comparison of methods for increasing compliance within a general practitioner based screening project for colorectal cancer and the effect on practitioner workload. Issue 1 (March 1988) - Pye, G; Christie, M; Chamberlain, J O; Moss, S M; Hardcastle, J D
Abstract : Screening for colorectal cancer by testing for faecal occult blood (FOBT) is effective for early diagnosis, but the success of a screening programme also depends on compliance. The aims of this study were to assess the effect of health education on compliance and to assess any addition to general practitioner workload that resulted. Altogether 3860 patients were recruited and randomly allocated to test or control group. The test group was further divided into subgroups, some of which received health education. Compliance with FOBT was 54.7% (210/384) in the subgroup receiving only the doctor's letter, which fell to 48.1% (743/1544) in the group receiving health education. General practitioner consultation rates were similar in test and control groups.